Hydrogen peroxide triggers an increase in cell surface expression of system xc− in cultured human glioma cells. (March 2020) - Chase, Leah A.; VerHeulen Kleyn, Mary; Schiller, NaTasha; King, Abby Goltz; Flores, Guillermo; Engelsman, Sasha Balcazar; Bowles, Christina; Smith, Sara Lang; Robinson, Anne E.; Rothstein, Jeffrey
Abstract: System xc − exchanges extracellular cystine for intracellular glutamate across the plasma membrane of many cell types. One of the physiological roles of System xc − is to provide cystine for synthesis of the antioxidant glutathione. Here we report that hydrogen peroxide (H2 O2 ) triggers the translocation of System xc − to the plasma membrane within 10 min of the initial exposure. Specifically, we observed a three-fold increase in 35 S-l -cystine uptake following a 10 min exposure to 0.3 mM H2 O2 . This effect was dose-dependent with an EC50 for H2 O2 of 65 μM. We then used cell surface biotinylation analysis to test the hypothesis that the increase in activity is due to an increased number of transporters on the plasma membrane. We demonstrated that the amount of transporter protein, xCT, localized to the plasma membrane doubles within 10 min of H2 O2 exposure as a result of an increase in its delivery rate and a reduction in its internalization rate. In addition, we demonstrated that H2 O2 triggered a rapid decrease in total cellular glutathione which recovered within 2 h of the oxidative insult. The kinetics of glutathione recovery matched the time course for the recovery of xCT cell surface expression and System xc − activity following removal of the oxidative insult. Collectively, these results suggest that oxidants acutely modulate the activity of System xc − by increasing its cell surface expression, and that this process may serve as an important mechanism to increase de novo glutathione synthesis during periods of oxidative stress. Highlights: System xc - activity is acutely regulated by physiological levels of hydrogen peroxide. Oxidative stress induces a rapid increase in xCT cell surface expression. H2 O2 exposure increases xCT membrane delivery rate and reduces its internalization rate. Increases in System xc - cell surface expression persist only until glutathione levels recover.